High electromechanical performance of modified electrostrictive polyurethane three-phase composites. (12th April 2018) - Ardimas,; Putson, Chatchai; Muensit, Nantakan
Abstract: In order to enhance the electrostrictive polymer, the polyurethane has been modified with conductive fillers that are promising for actuator applications, energy conversion, and sensors. The polyurethane (PU) matrix and the conductive fillers such as graphene nanosheets (GRN) and polyaniline nanopowder (PANI) were prepared to gain films by solution casting method. The morphology, structure and thermal behavior of PU three-phase composite were observed by SEM imaging, FTIR, and DSC techniques. In addition, the electrical and mechanical properties of polyurethane filled with both composites were investigated by an LCR meter and strain gauge setup. In order to study the electrostriction behavior, the electric field induced strain of PU three-phase composite films was monitored via lock-in amplifier at a low frequency of 1 Hz. A greater electrostriction effect of the PU three-phase composites at low electric field significantly related with contribute to conduction and interfacial polarization base on space charges distribution, filler-filler network and microstructure on crystallinity in the HS domain of PU matrix. Therefore, electrostriction behavior in the PU three-phase composites has been discussion. It was known that why the three-phase composites can provide high electromechanical performance for actuator applications.